2020
DOI: 10.1093/bjs/znaa007
|View full text |Cite
|
Sign up to set email alerts
|

Recovery after breast cancer surgery following recommended pre and postoperative physical activity: (PhysSURG-B) randomized clinical trial

Abstract: Background The effect of preoperative physical activity on recovery and complications after primary breast cancer surgery is unknown. The objective of this trial was to evaluate whether a recommendation of non-supervised physical activity improved recovery after breast cancer surgery. Methods This parallel, unblinded, multicentre interventional trial randomized women in whom breast cancer surgery was planned. The intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 26 publications
3
33
0
Order By: Relevance
“…Most studies (39 of 57) were RCT [ 19 57 ], five were controlled non randomized clinical trials [ 58 63 ], four were prospective cohort studies [ 61 , 64 66 ], one was a retrospective cohort study [ 67 ], two was a case–control study [ 68 , 69 ], four were quasi-experimental [ 70 – 73 ], one was a pilot study [ 74 ] and one was a feasibility study [ 75 ]. The studies originated from 22 countries distributed across 4 continents (i.e., Americas, Europe, Asia and Oceania), most of which were high income countries [ 19 26 , 29 , 31 , 33 – 36 , 39 41 , 44 47 , 50 , 52 54 , 56 , 57 , 59 , 61 – 69 , 71 , 73 75 ] or upper-middle income countries [ 27 , 28 , 30 , 32 , 37 , 38 , 42 , 43 , 48 , 49 , 58 , 60 , 72 ], with only three studies conducted in lower-middle income countries [ 51 , 55 , 70 ]. The body of literature on this topic turned out to be quite recent, with 71.9% (41 of 57) of studies published between 2010 and 2022 and 22.8% (13 out of 57) between 2000 and 2009.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies (39 of 57) were RCT [ 19 57 ], five were controlled non randomized clinical trials [ 58 63 ], four were prospective cohort studies [ 61 , 64 66 ], one was a retrospective cohort study [ 67 ], two was a case–control study [ 68 , 69 ], four were quasi-experimental [ 70 – 73 ], one was a pilot study [ 74 ] and one was a feasibility study [ 75 ]. The studies originated from 22 countries distributed across 4 continents (i.e., Americas, Europe, Asia and Oceania), most of which were high income countries [ 19 26 , 29 , 31 , 33 – 36 , 39 41 , 44 47 , 50 , 52 54 , 56 , 57 , 59 , 61 – 69 , 71 , 73 75 ] or upper-middle income countries [ 27 , 28 , 30 , 32 , 37 , 38 , 42 , 43 , 48 , 49 , 58 , 60 , 72 ], with only three studies conducted in lower-middle income countries [ 51 , 55 , 70 ]. The body of literature on this topic turned out to be quite recent, with 71.9% (41 of 57) of studies published between 2010 and 2022 and 22.8% (13 out of 57) between 2000 and 2009.…”
Section: Resultsmentioning
confidence: 99%
“…Exercises targeting upper limb tissues and function were predominant. Fewer studies adopted a more global approach, providing aerobic exercises [ 21 , 23 , 52 , 66 , 71 ] or yoga [ 41 , 55 ], as well as strengthening or stretching of the lower extremity [ 19 21 ] or neck muscles [ 28 , 44 , 57 , 58 , 60 63 , 66 , 72 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We report 4 weeks and 12 months follow-up data from the PhysSURG-B randomised, controlled, prospective interventional trial evaluating an intervention of added aerobic physical activity before and after breast cancer surgery. The study protocol and primary outcome of self-reported physical recovery at 4 weeks after surgery have been published elsewhere [16]. Participants were recruited from three surgical departments in the Western Region of Sweden between Nov 2016 and Dec 2018.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…The intervention in the PhysSURG-B trial has been described previously in detail [16]. In summary, patients in the intervention group received an individual consultation with a physiotherapist and were instructed to add 30 minutes of daily aerobic physical activity, 2 weeks ±1 week before and 4 weeks after breast cancer surgery.…”
Section: Intervention and Controlmentioning
confidence: 99%